Investigation of an effective method for cooling of an air-cooled condenser - Abu Bakar Mohammad (2023)
Cooling system in power plant plays important roles as it can affect overall efficiency of the plant. This paper investigates an Air Cooled Condenser (ACC) unit under bad working condition which during hot season. The ACC model os simulated using computional fluid dynamics (CFD) software.